Performance, Expenses and Funds Flows: Evidence from the Greek Mutual Fund Market - G Rompotis, Gerasimos (International Journal of Management Excellence (ISSN: 2292-1648), 2014)
This paper examines the factors that affect performance, expense ratios and flows of Greek equity mutual funds during 2002-2005 and provides possible explanations for the rare phenomenon of a stagnated mutual fund market in the midst of growing capital markets in Greece and elsewhere. Results demonstrate strong economies of scale for expenses, a negative relationship between performance and expense ratio, funds flow reduction (increase) with increases in expenses (fund age and fund family), and a significant unexplained portion of funds flows. Also discovered is the inadequate competition due to large load fees and expense ratios of two to three times greater than those in other developed markets and a tradeoff between expense ratio and performance of 1.45 instead of 1 which has been observed in the literature.